Multilingual acquisition of determiner phrases in L2 English and L3 French by L1 Swahili speakers in Tanzania - Nyakana, Deniza Joash (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.